2011
DOI: 10.1111/j.1440-1746.2011.06759.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic, clinicopathological features and prognosis of very young patients with gastric cancer

Abstract: The study describes that very young patients with gastric cancer were mainly females, who were less likely to present with alarm features, but had a high frequency of family history of gastric cancer; and the majority of these cancers were located in gastric body, and they had similar long-term prognosis compared with elderly counterparts if curative surgical resection was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 24 publications
(36 reference statements)
4
33
0
Order By: Relevance
“…1 However, most previous studies on young gastric cancer patients showed a female predominance, with a lower male-to-female sex ratio (0.54:1∼1.26:1). 3,6,9,10,13 The male-to-female sex ratio of young gastric patients who underwent ESD was 0.77:1 in our study. This corresponds to findings in young gastric patients with not only advanced stage but also early stage of disease.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…1 However, most previous studies on young gastric cancer patients showed a female predominance, with a lower male-to-female sex ratio (0.54:1∼1.26:1). 3,6,9,10,13 The male-to-female sex ratio of young gastric patients who underwent ESD was 0.77:1 in our study. This corresponds to findings in young gastric patients with not only advanced stage but also early stage of disease.…”
Section: Discussionmentioning
confidence: 80%
“…14,15 Especially, a positive family history of gastric cancer correlates with younger age, 15 and the rate of positive family history of gastric cancer in young gastric cancer patients ranged from 5.9% to 19.3%. 3,6,10,13 Like other studies on young gastric cancer patients including those with advanced-stage gastric cancer, relatively higher rates of young patients with early-stage disease (12.5%) had a positive family history of gastric cancer in first-degree relatives, and less than half the patients had a smoking history and about half of the patients had a history of alcohol consumption. In previous studies, tumors located in the middle third, with a flat or depressed morphology, of the diffuse type according to Lauren's classification, and with undifferentiated type histology were more common in young gastric cancer patients than in older patients.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations